THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR TOWARDS OFFICER PERFORMANCE WITH THE ORGANIZATION AND RELIGIOSITY AS A MODERATING VARIABLE (STUDY ON THE EMPLOYEES OF THE EDUCATION AND CULTURE DEPARTMENT IN DEMAK) - Erika Bestyasamala (IJIBE (International Journal of Islamic Business Ethics), 2018)
Performance is always the problem faced by government organizations, so it is necessary to know the factors that affect the performance of employees. This research aims to test the influence of emotional intelligence and organizational citizenship behavior on employee performance with a moderated Climate organization and Religiosity in the service of education and culture of Demak Regency. This research uses a quantitative approach to Explanatory research. The population in this research is a Muslim employee perform duties in the service of education and culture of Kab. Demak and with a population of 117 people. The variable in this study consists of three free variables that is emotional intelligence (X 1), Organizational Climate (X 2), Religiosity (X 3) and two variable i.e. Organizational Citizenship Behavior (Y1) and the performance of the Employee (Y2). Data collection using a structured questionnaire tool is closed and the results of the data collection further analyzed by using Multiple Linear Regression equations model. The research results showed that significant positive Emotional effect on performance, Organizational Citizenship Behavior significant negative effect on performance, emotional intelligence a significant positive effect against the performance of employees, Organizational Climate strengthens the influence of emotional intelligence on employee performance, Religiosity weakens the influence of emotional intelligence to increased Employee Performance, strengthen the influence of Religiosity Organizational Citizenship Behavior (OCB) against performance improvement Officer Office of education and culture of Demak Regency.Keyword: Employee Performance, Emotional Intelligence, Organization Climate, Religiosity, Organizational Citizenship Behavior.